2015
DOI: 10.1111/jon.12275
|View full text |Cite
|
Sign up to set email alerts
|

Corpus Callosum Diffusion and Language Lateralization in Patients with Brain Tumors: A DTI and fMRI Study

Abstract: BACKGROUND AND PURPOSE Examining how left-hemisphere brain tumors might impact both the microstructure of the corpus callosum (CC) as measured by fractional anisotropy (FA) values in diffusion tensor imaging (DTI) as well as cortical language lateralization measured with functional MRI (fMRI). METHODS fMRI tasks (phonemic fluency and verb generation) were performed in order to detect activation in Broca’s and Wernicke’s area. Twenty patients with left-hemisphere brain tumors were investigated. fMRI results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 18 publications
3
24
0
Order By: Relevance
“…This is in line with the recent study done by Tantillo et al, which observed that FA values were higher in left‐hemispheric brain tumor patients that were codominant for language tasks than those that were left‐dominant, and this was suspected to be due to contralateral brain reorganization in the codominant group. Although contralateral reorganization is usually associated with low‐grade gliomas because of their typically longer median survival time compared to HGGs, contralateral reorganization has been suggested to occur in HGG patients as well . In addition, the median survival time for HGG patients is known to be longer than that for MET patients, so our results provide further evidence that a higher degree of contralateral brain reorganization can occur if the brain is given more time to undergo reorganization.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in line with the recent study done by Tantillo et al, which observed that FA values were higher in left‐hemispheric brain tumor patients that were codominant for language tasks than those that were left‐dominant, and this was suspected to be due to contralateral brain reorganization in the codominant group. Although contralateral reorganization is usually associated with low‐grade gliomas because of their typically longer median survival time compared to HGGs, contralateral reorganization has been suggested to occur in HGG patients as well . In addition, the median survival time for HGG patients is known to be longer than that for MET patients, so our results provide further evidence that a higher degree of contralateral brain reorganization can occur if the brain is given more time to undergo reorganization.…”
Section: Discussionsupporting
confidence: 92%
“…Since this seems to occur more in the patients of the HGG group according to their DTI characteristics, this raises the possibility that the increase in interhemispheric transfer would be due to more excitatory signals being sent to the contralateral side through the CC . Higher FA values of the CC have been shown to occur in those with bimanual motor skills or codominant language tasks as compared to more lateralized individuals, which further supports this speculation …”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Structural changes have been demonstrated within the corpus callosum in functional MRI in patients with left hemispheric brain tumours impacting normal centres of language processing and production. These differences suggest network plasticity resulting in dysfunctional recruitment of the non-dominant hemisphere 4. Peters et al 2 presented a patient with new onset stuttering after recurrence of a right temporoparietal anaplastic astrocytoma, suggesting an additional complex interplay between cortical and subcortical structures in the role of language.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, it is possible that the involvement of varying degrees of white matter surrounding the basal ganglia could factor in establishing co-dominance for language. The corpus callosum for example, has been correlated with co-dominance in brain tumor patients (Tantillo et al, 2015). However, the corpus callosum specifically was only involved in two of our thirty-five co-dominant cases, lessening its contribution.…”
Section: Discussionmentioning
confidence: 99%